Complications and In-Hospital Mortality After On- Pump Vs Off-Pump Coronary Artery Bypass Grafting - Janashia, Giorgi; Chkaidze, Zurab; Nachkepia, Merab; Beselia, Kakha; Taboridze, Iamze (European Scientific Journal, ESJ, 2018)
Off-pump surgery has involved into the most frequently adopted alternative technique to conventional on-pump coronary artery bypass grafting (CABG) in the treatment of patients with coronary artery disease. Our aim was to compare data analyses of complications and in-hospital mortality after on-pump vs off-pump CABG. Materials and methods: Retrospective data analyses research is based on 402 patients, ranging in 37-75 years of age. Operations CABG were performed in 2009- 2012, at the West Georgian Interventional Medicine National Center Hospital, Kutaisi; Aleksandre Aladashvili Clinic, Tbilisi; and L.T.D. Lancet, Tbilisi. 253 cases were performed off pump and 149 cases were performed on pump. Groups were diversified by the F Fischer’s criteria. Odds ratio (OR) was made using regression analysis. Statistical analysis was made using SPSS 22 program. Results: While on pump during surgery, intraoperative shock occurred in 8(5.37%) cases, Thrombosis – 3(2.01%); Dissection – 3(2.01%), Stroke – 1(0.67%) and Myocardial Infarction – 1(0.67%). These complications were not detected during off pump CABG. Frequency of in-hospital mortality after off pump and on pump CABG are respectively 7(2.77%) and 15(10.07%) - p<0.0018. Totallyperi operative complications were during off pump CABG – 35(13.83%) and on pump CABG – 41(27.51%)(p<0.0007). In the cases of on pump surgery, odds ratio of complications that arise: bleeding OR=4.48(95CI;1.38-14.54); atrial fibrillation – OR=6.64(95%CI:1.82-24.21); pulmonary complications - OR=2.24(95%CI:1.19-4.21), renal insufficiency - OR=8.75(95%CI:1.01- 75.63); in-hospital mortality – OR=2.365(95%CI:1.425-3.924). Conclusion: Off pump CABG seems to significantly reduce postoperative renal failure, bleeding, atrial fibrillation, and respiratory complications, while perioperative myocardial infarction rates remain significantly unchanged. Considering in-hospital mortality and perioperative complications, off pump CABG has much better results.